Supply and demand for livestock credit in sub-Saharan Africa: Lessons for designing new credit schemes - Jabbar, M.A.; Ehui, Simeon K.; Kaufmann, Ralph R. von (Elsevier, 2002)
Based on analysis of credit supply in Ethiopia, Kenya, Uganda and Nigeria, it is shown that public credit institutions do not have sufficient funds to meet the demand for livestock credit and cannot mobilize savings from their clients or other commercial sources for one reason or another. In addition, available credit does not reach those who need it the most and with whom it could have the greatest impact due to the application of inappropriate screening procedures and criteria to determine creditworthiness. The analysis of demand based on borrowing and nonborrowing sample households using improved dairy technology, it is shown that not all borrowers borrowed due to liquidity constraint while some borrowers and some nonborrowers had liquidity constraint but did not have access to adequate credit. Logistic regression analysis show that sex and education of the household head, training in dairy, prevalence of outstanding loan and the number of improved cattle on the farm had significant influence on both borrowing and liquidity status of a household, though the degree and direction of influence were not always the same in each study country. Based on the findings it is suggested that combining public and commercial finance could solve the problem of inadequate credit supply while inventory finance to community level input suppliers and service providers might help in getting credit to worthy and needy smallholders at lower cost than providing credit to smallholders directly.